Faktor-Faktor yang Mempengaruhi Brand Loyalty pada Sepatu Lokal Indonesia - Primandaru, Noormalita; Kristiani, Nuning; Pareallo, Pian (Universitas Hayam Wuruk Perbanas, 2022)
The research conducted has the purpose to examine the effect of brand identity on consumer brand loyalty of Geoff Max footwear, the effect of brand attachment on consumer brand loyalty of Geoff Max footwear, and the influence of brand image on brand loyalty. This research is a survey research with a questionnaire in the form of a Google form as an instrument in this study. The sample in this study was Yogyakarta students who wore Geoff Max shoes, totaling 152 respondents. Data testing using SPSS. The results of the study found that brand identity had a positive but not significant effect on consumer brand loyalty Geoff Max footwear, brand attachment had a positive and significant effect on consumer brand loyalty Geoff Max footwear, and brand image had a positive and significant effect on consumer brand loyalty. Geoff Max shoes. Through this research, it is expected that it can share useful information and can provide some suggestions regarding brand identity, brand attachment, brand image, and brand loyalty from a student perspective for Geoff Max Footwear in developing his business.